Peluang Dan Tantangan Penerapan Hukum Pidana Islam Di Kota Padangsidimpuan - Hendra Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
This paper will export the opportunities and challenges of the application of Islamic criminal law in Padangsidimpuan City, in which this writer uses a qualitative method by direct observation to the field by interviewing people and community leaders, sub-district heads, and community organizations. In this paper we find information about the application of Islamic criminal law in the City of Padangsidimpuan apparently lacking opportunities but more challenging because the population of the City of Padangsidimpuan consists of several recognized religions in Indonesia.